Embedment of Steel Spiral Cases in Concrete: Lessons from a Structural Deformation Accident in China - Xiaofeng Gao; Dan Fu; Hegao Wu (Applied Sciences, 2022)
A spiral case structure (SCS) plays a significant role in the safe and reliable operation of a hydroelectric power plant (HPP). In an HPP with 700 MW class turbine in China, a structural deformation accident happened in the construction period causing severe loss. Based on in-situ measured data, this study focuses on two major differences of this SCS that might cause the accident: (a) the construction condition, and (b) the shape of steel spiral case (SSC). The accident is reproduced in numerical study, and the simulation results agree reasonably well with in-situ measured data. The results show that the construction condition is a main factor causing the accident, but it is not the only cause of the raising deformation. The findings reveal that the post-accident stresses of steel structures are still at a relatively low level, and it would not be a major concern. The study also shows that the SSC with non-circle sections tends to have larger deformation under internal water pressure, and the deformation of the stay ring needs more attention in the construction period. The major limitation of this study is that this study merely focuses on the construction period. If such SCSs were to be used in a wider range, a follow-up study focusing on the operation period should be considered.